2009
DOI: 10.1080/17429140802503343
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-oriented isolation of an insecticide from Ailanthus altissima

Abstract: The tree-of-heaven, Ailanthus altissima Swingle(Simaroubaceae), was studied for its potential insecticide activity against the pea aphid, Acyrtosiphon pisum (Harris). First instar aphids were dipped in water solutions of root extract and of leaf extract of A. altissima, and this was followed by bioassay-oriented fractioning of leaf extract (more active in bioassays) with petroleum ether, chloroform, chloroform-methanol, methanol and water, and of chromatographic fractions. The putative active constituent ailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Plant secondary metabolites play an important role in plantinsect interactions and therefore such compounds may have insecticidal, hormonal, and antifeedant activities against insects (De Feo et al 2009). From an ecological perspective, such compounds can be considered as chemical weapons to ward off predators and competitors for limited resources and contribute to explaining the ecological impact of A. altissima in ecosystems (De Feo et al 2009). A. altissima presents a strong resistance to herbivores (insects), due to the chemical composition of its tissues.…”
Section: Insecticide Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…Plant secondary metabolites play an important role in plantinsect interactions and therefore such compounds may have insecticidal, hormonal, and antifeedant activities against insects (De Feo et al 2009). From an ecological perspective, such compounds can be considered as chemical weapons to ward off predators and competitors for limited resources and contribute to explaining the ecological impact of A. altissima in ecosystems (De Feo et al 2009). A. altissima presents a strong resistance to herbivores (insects), due to the chemical composition of its tissues.…”
Section: Insecticide Effectmentioning
confidence: 99%
“…Botanical pesticides are of increasing interest today, due to the problems related to the negative effects of conventional pesticides on the environment and the beneficial fauna (De Feo et al 2009). A review of sublethal effects, taking into account recent data, has revealed new insights into the effects of pesticides, including influences on learning performance, behavior, and neurophysiology (Desneux et al 2007).…”
Section: Insecticide Effectmentioning
confidence: 99%
See 3 more Smart Citations